A REVIEW OF THE EVENT INDUSTRY’S IMPACT AND CRISIS MANAGEMENT ANALYSIS DURING COVID-19 - Noor Zeti Aiqa Mad Isa; Eiren Sarah Emran; Nor Syahirah Azmi; Nur Afiqah Mohd Azan; Norlida Zakirai@Zakaria (International Journal of Accounting, Finance and Business, 2022)
This paper will review the impact of event’s industry and the crisis management analysis during COVID-19. The hospitality and event industry were the most affected since government of many countries’-imposed restriction of travelling by closing the borders to slow the spread of the outbreak. This pandemic gives the greatest challenges to tourism and event’s industry because this industry relies on a large group of people’s gathering. This paper will scrutinize the holistic impact of COVID-19 outbreak since world’s view this pandemic give threat to human and livelihood after Second World War. Apart from that, this review also intent to highlight crisis management analysis undertake by event’s industry as a recovery process. A search of literature has been conducted through reputable electronic databases namely Scopus, ScienceDirect and ProQuest to search for the publish articles between year 2019-2022 in order to analyse past research on the topics. Findings of the review indicated that, the impact of pandemic affected event’s industry economically that incur lost to employment, organization bankruptcy as well as disruption in supply chain. However, there is an opportunity arise to sustain the relevancy of event industry by emerging of technology to support virtual event. The crisis management analysis aids organization to oversee and forecast various planning to deal with disaster in the future.